Pengaruh Kebijakan Moneter Terhadap Inflasi di Indonesia - Anisa Nashwa Natania; Yollit Permata Sari (Universitas Negeri Padang, 2025)
Inflation is one of the key economic indicators that reflects the general increase in the prices of goods and services. Monetary policy plays a crucial role in controlling inflation through instruments such as interest rates, exchange rates, and money supply. This study aims to analyze the impact of monetary policy on inflation in Indonesia using quarterly time series data from the period 1993–2024. The analytical method employed is multiple linear regression with the Ordinary Least Squares (OLS) approach after ensuring data stationarity through the Augmented Dickey-Fuller (ADF) test. The findings indicate that (1) interest rates have a negative and significant effect on inflation, with a coefficient of -0.0424 (p-value = 0.0000), meaning that an increase in interest rates can suppress inflation. (2) The money supply has a positive and significant effect on inflation, with a coefficient of 4.1602 (p-value = 0.0094), indicating that an increase in money supply tends to raise inflation. Meanwhile, (3) the exchange rate does not have a significant effect on inflation (p-value = 0.1726). The F-test results show that the overall regression model is significant (p-value = 0.000004), with an R² value of 20.25%, meaning that the monetary policy variables used in this study explain only a small portion of the variation in inflation in Indonesia.